IMPLEMENTASI KAIDAH-KAIDAH FIKIH PADA HUKUM EUTHANASIA - Mardhatillah Ali; Ashar Pagala (Minhaj: Jurnal Ilmu Syariah, 2023)
According to medical science, euthanasia is a method for patients whose condition is on the verge of dying, in which the purpose is to cease their sufferings. This means, it will accelerate the patient's death. It is divided into two, which are active euthanasia (an injection or medicine given by a doctor to a patient to accelerate his / her death). It is actually haram, since it is considered as intentional murder. That idea is supported when applying the principles of jurisprudence, which are a branch of al-?araru yuz?l (threat should be avoided), even though in the process of applying these rules, there are still contradictions. However, they can be denied by saying that to murder a person is the worst threat which must be avoided, since Allah is supposedly the only one who has control over life and death. As for the second type of euthanasia, it is passive euthanasia; which is done by stopping to treat a patient with a serious illness who has zero chance to recover, hence they will pass away faster. This one is considered jaiz (permissible); since the original law in treatment is Sunna.